Intelligent real-time rendering - Wong, Gabriyel Chee Kien (2014)
The perennial and increasing demand for fidelity in real-time computer graphics, coupled with hardware architecture advancement, pose many challenges to researchers as they endeavour to find the optimal solution to accommodate both speed of rendering and quality in interactive rendering applications.